Impact and Delamination Failure of Multiscale Carbon Nanotube-Fiber Reinforced Polymer Composites: A Review - Khan, Shafi Ullah; Kim, Jang-Kyo (International journal of aeronautical and space sciences, 2011)
Fiber reinforced polymer composites (FRPs) are being increasingly used for a wide range of engineering applications owing to their high specific strength and stiffness. However, their through-the-thickness performance lacks some of the most demanding physical and mechanical property requirements for structural applications, such as aerospace vehicles and military components. Carbon nanotubes (CNTs) and carbon nanofibers (CNFs), due to their excellent mechanical, thermal and electrical properties,offer great promise to improve the weak properties in the thickness direction and impart multi-functionality without substantial weight addition to FRPs. This paper reviews the progress made to date on i) the techniques developed for integration of CNTs/CNFs into FRPs, and ii) the effects of the addition of these nanofillers on the interlaminar properties, such as such interlaminar shear strength, interlaminar fracture toughness and impact damage resistance and tolerance, of FRPs. The key challenges and future prospects in the development of multiscale CNT-FRP composites for advanced applications are also highlighted. KCI Citation Count: 2